Preliminary examination of embezzlement reports of housing and public utilities budget funds - Andrey Vladimirovich Borbat, Gyunay Aladdinovna Alieva, Ekaterina Nikolaevna Arestova,; Burmistrov, Igor Alekseevich; Zeynalova, Larisa Mikhailovna; Tatyana Nikolaevna Sinyukova, Elena Anatolevna Mironova, (Opción, 2019)
The urgency of the problem under investigation is caused by the issues arising in the course of the preliminary investigation of corruption crimes in the sphere of housing and public utilities, including theft of budget funds. In this regard, this article is aimed at a comprehensive analysis of examples from investigative practices, addresses the issue of single cases of bringing officials for crimes of this category to justice. The materials of the article can be used both for law enforcers and for students, undergraduates, and postgraduates studying in the direction of "Jurisprudence"